Non-Institutional Market Making Behavior: The Dalian Futures Exchange - Oscar Jordá; Holly Liu; Jeffrey Williams (University of California, Department of Economics, 2002)
This paper contains three useful contributions: (1) it collects a new data-set of electronic transaction data on soybean futures from the Dalian Futures Exchange in China that records, not only the usual elements of each transaction (such as price and size) but also identifies broker and customer identities, variables not usually obtainable; (2) it presents new econometric methods for the analysis of dynamic multivariate count data based on the autoregressive conditional intensity model of Jord\~A and Marcellino (2000); and (3) together, the new data and econometric methods allow us to investigate, in a manner not available before, the determinants and effects of non-institutional market making (or scalping).
Keywords: G13; G14; C32; 330; market making; autoregressive conditional intensity; high-frequency data; Rohstoff-Futures; Sojabohne; Anlageverhalten; Volatilität; Gesamtwirtschaftliche Liquidität; China